Dependence of Atmospheric Transport Into the Arctic on the Meridional Extent of the Hadley Cell. Issue 20 (24th October 2020) - Yang, Huang; Waugh, Darryn W.; Orbe, Clara; Chen, Gang
Abstract: Recent studies have shown a large spread in the transport of atmospheric tracers into the Arctic among a suite of chemistry climate models and have suggested that this is related to the spread in the meridional extent of the Hadley Cell (HC). Here we examine the HC‐transport relationship using an idealized model, where we vary the mean circulation and isolate its impact on transport to the Arctic. It is shown that the poleward transport depends on the relative position between the northern edge of the HC and the tracer source, with maximum transport occurring when the HC edge lies near the middle of the source region. Such dependence highlights the critical role of near‐surface transport by the Eulerian mean circulation rather than eddy mixing in the free troposphere and suggests that variations in the HC edge and the tracer source region are both important for modeling Arctic composition. Plain Language Summary: Long‐range transport plays a crucial role in determining the distribution of pollutants in the Arctic, as many pollutants have their sources in northern middle latitudes. Recent studies show large differences in transport into the Arctic among models, and it has been suggested that this is related to differences in the northern edge of the Hadley Cell (HC) in the models. We revisit this topic using an idealized model in which the extent of the HC can be varied in a controlled manner. We show that the relative position between the tracer source and the northern edge of the HC plays an important role in determining how rapidly air is transported into the Arctic. The most rapid transport occurs when the HC edge lies near the middle of the tracer source region. This results suggest that variations in the HC edge and the tracer source region are both important for modeling Arctic composition. Key Points: Transport of tracers from the northern midlatitude surface into the Arctic is sensitive to changes in the northern edge of the Hadley Cell The relative position between a tracer source and the Hadley Cell edge plays a major role in the transport into the Arctic Differences in the poleward transport are mainly due to differences in the near‐surface mean flow rather than mixing in the free troposphere